Energy, exergy, exergoeconomic, and exergoenvironmental study of a parabolic trough collector using a converging-diverging receiver tube. (25th June 2019) - Okonkwo, Eric Chekwube; Ratlamwala, Tahir Abdul Hussain; Abid, Muhammad
This study presents a novel energy, exergy, exergoeconomic and exergoenvironmental analysis of a parabolic trough collector operating with a converging-diverging absorber tube design. The collector is modelled thermally after the experimental results of the Sandia National Laboratory LS-2 collector test using the engineering equation solver. The results show that the converging-diverging geometry obtained a mean enhancement of 1.13% and 0.49% for the energy and exergy efficiencies respectively. The optical losses accounted for 24.5% of the exergetic losses while 59.7% of the exergy destruction is due to heat transfer between the sun and the absorber. The exergoeconomic study shows that the cost rate of exergy destruction is seen to decrease from 3.4-0.35 $/hr as the inlet temperature increases from 323-650 K. The environmental study yielded an exergoenvironmental impact factor of 0.31 with the values of 2.61 and 1.22 for the exergoenvironmental impact coefficient and impact improvement respectively.